Binding brain better—matching var genes and endothelial receptors - Hannah Fleckenstein; Silvia Portugal (EMBO Molecular Medicine)
Abstract Cerebral malaria remains a major cause of death for African children, and mechanistic insights regarding the establishment of brain pathology are greatly needed. Expression of specific domains of parasite's var genes promoting brain adhesion of infected erythrocytes had been previously identified, but binding specificities and the receptor preference in the brain endothelial cells had not been fully described. The study by Storm et al (2019) in this issue of EMBO Molecular Medicine demonstrates that binding to brain endothelial cells via EPCR and ICAM‐1 is increased in parasites causing cerebral malaria compared to parasites causing uncomplicated malaria. Furthermore, expression levels of var genes encoding the CIDRα1 domain with EPCR affinity correlate with the receptor‐dependent binding to brain, but not dermal endothelial cells, highlighting the important role of EPCR in cerebral malaria pathology.